2018
DOI: 10.1021/acs.jpcc.8b06459
|View full text |Cite
|
Sign up to set email alerts
|

CsxFA1–xPb(I1–yBry)3 Perovskite Compositions: the Appearance of Wrinkled Morphology and its Impact on Solar Cell Performance

Abstract: We report on the formation of wrinkle-patterned surface morphologies in cesium formamidinium based Cs x FA 1-x Pb(I 1-y Br y) 3 perovskite compositions with x = 0-0.3 and y = 0-0.3 under various spin-coating conditions. By varying the Cs and Br content, perovskite precursor solution concentration, and spin-coating procedure, the occurrence and characteristics of the wrinkleshaped morphology can be tailored systematically. Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17) 3 perovskite layers were analyzed regarding their surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 77 publications
(202 reference statements)
3
37
0
Order By: Relevance
“…The devices were not subjected to any pre‐conditioning. In order to average over possible slight variations in the EQE spectra of the bottom c‐Si and CIGS cells when measured below the perovskite filters, which can be induced by inhomogeneous scattering and transmission properties due to typical thickness variations of double‐cation FA 0.83 Cs 0.17 Pb(I 1− y Br y ) 3 perovskite films (“wrinkle structure,” compare Braunger et al and Bush et al), [ 111,112 ] a large illumination spot was used. The absolute EQE values and hence integrated J SC of the CIGS bottom cells were corrected to account for the finger lines of the metal grid (shading effect).…”
Section: Methodsmentioning
confidence: 99%
“…The devices were not subjected to any pre‐conditioning. In order to average over possible slight variations in the EQE spectra of the bottom c‐Si and CIGS cells when measured below the perovskite filters, which can be induced by inhomogeneous scattering and transmission properties due to typical thickness variations of double‐cation FA 0.83 Cs 0.17 Pb(I 1− y Br y ) 3 perovskite films (“wrinkle structure,” compare Braunger et al and Bush et al), [ 111,112 ] a large illumination spot was used. The absolute EQE values and hence integrated J SC of the CIGS bottom cells were corrected to account for the finger lines of the metal grid (shading effect).…”
Section: Methodsmentioning
confidence: 99%
“…Braunger et al also reported the formation of wrinkled perovskite morphology based on Cs x FA 1− x Pb(I 1− y Br y ) 3 composition by optimizing the contents of Cs and Br, precursor solution concentration and spin‐coating parameters. It is proposed that the formation of wrinkled morphologies is stemmed from the release of compressive strain within the perovskite film …”
Section: Strategies To Prepare Diverse Perovskite Morphologiesmentioning
confidence: 99%
“…Braunger et al reported the PSCs based on wrinkled perovskite morphology, which exhibited improved PCE up to 17% as compared to that of flat perovskite morphology‐based device (PCE = 14.7%). The improved PCE can be attributed to the enhanced light harvesting and suppressed nonradiative combination originated from the wrinkled perovskite morphology . We for the first time fabricated the novel bilayered MAPbI 3 perovskite film featuring a maze‐like top layer and a dense bottom layer with the assist of MACl additive.…”
Section: Diverse Perovskite Morphologies For Optoelectronic Applicationsmentioning
confidence: 99%
“…In general, the external quantum efficiency (EQE) of efficient single-junction perovskite cells with opaque rear-mirror contacts (metal) is above 80% near the bandedge [17][18][19] , while that of semi-transparent cells show a lower value (around 70%) in the same spectral range 4,13,[20][21][22] . Employing high-quality and thick active layers to overcome insufficient photon absorption has advanced Sn-based perovskite solar cells 4,5,23 ; however, for Pb-based perovskites, thick films exhibit inhomogeneous morphologies 24,25 and limited carrier diffusion lengths [26][27][28] .…”
mentioning
confidence: 99%